2022
DOI: 10.1002/aesr.202200009
|View full text |Cite
|
Sign up to set email alerts
|

Hard‐Carbon Anodes for Sodium‐Ion Batteries: Recent Status and Challenging Perspectives

Abstract: Sodium‐ion batteries (SIBs) hold great potential in the application of large‐scale energy storage. With the coming commercialization of SIBs, developing advanced anode of particularly hard carbon is becoming increasingly urgent yet challenging. Hard carbon still suffers from unclear sodium storage mechanism, unsatisfactory performance, and low initial Coulombic efficiency (ICE). Herein, the current state‐of‐the‐art advances in designing hard carbon anodes for high‐performance SIBs is summarized. First, the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 213 publications
0
22
0
Order By: Relevance
“…[ 50 ] The Raman spectra of the HCP powders are given in Figure 3c, and all samples exhibit two characteristic peaks at ≈1348 and ≈1590 cm −1 related to the D‐band and the G‐band, respectively. [ 8 ] It is known that the D‐band corresponds to the disordered carbon structure and G‐band is related to the graphitized carbon in the samples. [ 51 ] The intensity ratio between the G and D bands ( I G / I D ) is generally used to determine the degree of defectiveness and disorder in the carbons under study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 50 ] The Raman spectra of the HCP powders are given in Figure 3c, and all samples exhibit two characteristic peaks at ≈1348 and ≈1590 cm −1 related to the D‐band and the G‐band, respectively. [ 8 ] It is known that the D‐band corresponds to the disordered carbon structure and G‐band is related to the graphitized carbon in the samples. [ 51 ] The intensity ratio between the G and D bands ( I G / I D ) is generally used to determine the degree of defectiveness and disorder in the carbons under study.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Carbon materials have emerged as the most promising candidate for SIB anodes on account of their low cost, good electrical conductivity, and superior stability. [7][8][9][10] However, owing to their insufficient Na storage sites and low interlayer spacing, carbon anodes suffer from low capacity and sluggish kinetics. [11][12][13] It has been demonstrated that heteroatoms can supply a large number of Na storage sites through fast pseudo-capacitive reactions, which can simultaneously improve the capacity and rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the kinetic limitation of graphite to intercalate large Na + has not been met even with the top-notch advancements on the electrolyte front. The anodic intercalation of Na in the graphite is kinetically sluggish, besides being thermodynamically less productive. As a result, numerous types of electrodes suited for Na + storage in SIBs have been developed, including alloying type anode materials (Si, Sn, Sb), intercalation type anodes (titanium-based oxides), carbon-based anodes, and conversion type anodes (transition metal oxides, sulfides, and phosphides). Out of all these materials, hard carbons are regarded as the most promising for practical applications owing to their higher capacity (approaching commercial graphite in LIBs or even higher), high precursor availability, low cost, low insertion/deinsertion voltage, and safety. However, hard carbons mostly suffer from poor graphitization, leading to low electric conductivity, which reflects in impaired cycle life and poor rate capability. …”
Section: Introductionmentioning
confidence: 99%